Case Report: Dual Inhibition of HDAC and BTK for Diffuse Large B-Cell Lymphoma After Failure to CD19-Targeted CAR-T Therapy - Zhu, Weiguo; Tao, Shi; Miao, Wenchun; Liu, Hui; Yuan, Xianggui (Frontiers in Immunology, 2022)
Background: Failure to CD19-targeted chimeric antigen receptor T-cell (CAR-T) therapy for patients with relapsed/refractory (R/R) diffuse large B-cell lymphoma (DLBCL), is an emerging clinical problem. There is no consensus on the treatment for these patients and treatment remains empirical. Case report: We reported a case of an elderly R/R DLBCL patient who had TP53 mutation and relapsed 12 months after initial response to CAR T-cell therapy. The patient did not respond to salvage chemotherapy with the GDP regimen and could not tolerate any aggressive chemotherapy. Thereafter, the patient was given chidamide and zanubrutinib. After two months of treatment, the patient achieved sustained complete remission. At the last follow-up, the patient remains in metabolic CR 22 months after CAR-T infusion and 10 months after the initiation of the combination treatment. Conclusion: We report the first successful case of dual inhibition of HDAC and BTK for the treatment of R/R DLBCL after failure to CAR-T cell therapy, which opens a new therapeutic possibility for the future.